Attempted Inversion of Semiconducting Features of Platinum Polyyne Polymers: A New Approach for All‐Polymer Solar Cells. Issue 13 (16th May 2013) - Yuan, Yuping; Michinobu, Tsuyoshi; Oguma, Jun; Kato, Takehito; Miyake, Kunihito
Abstract: Platinum(II) polyyne polymers containing thiophene‐acceptor‐thiophene units are synthesized, and their main chain alkynes are functionalized by the formal cycloaddition–retro‐electrocyclization reaction with tetracyanoethylene (TCNE). The polymer energy levels are significantly decreased by the TCNE addition. Bulk‐heterojunction solar cells are fabricated using the TCNE‐adducted platinum(II) polyyne polymers. The use of these polymers as p‐type semiconductors in combination with n‐type fullerene derivatives indicates that the p‐type semiconducting ability decreases by approximately five to ten times after the TCNE addition. On the contrary, when the TCNE‐adducted polymers are employed as a substitute for the fullerene derivatives, the all‐polymer solar cells are initially fabricated. Abstract : Formal cycloaddition–retro‐electrocyclization reactions between platinum(II) polyyne polymers and tetracyanoethylene (TCNE) successfully lower the polymer energy levels. Application of these polymers to p‐type semiconducting materials in bulk‐heterojunction solar cells suggests that the p‐type performance decreases by approximately 5 to 10 times. Moreover, when a TCNE‐adducted polymer is employed as an n‐type semiconducting material, the generation of weak photocurrent is achieved.